Effect of Different Growth Regulators on Rooting of Cut Phylloclades of Opuntia elatjor Mill - Tanwar, G. S.; Sen, D. N. (Indian Forester)
Effect of exogenous supply of some wroth regulators like HA, IAA and NAA on rooting of cut phylloclades of Opuntia elotior, has been studied. Number of roots was maximum in lower concentration of NAA and the length in IAA, whereas number of laterals was found more in HA (100 ppm).